2017
DOI: 10.1016/j.shaw.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Quality of Occupational Health and Safety Management Systems Based on Key Performance Indicators in Certified Organizations

Abstract: BackgroundOccupational Health and Safety Management Systems are becoming more widespread in organizations. Consequently, their effectiveness has become a core topic for researchers. This paper evaluates the performance of the Occupational Health and Safety Assessment Series 18001 specification in certified companies in Iran.MethodsThe evaluation is based on a comparison of specific criteria and indictors related to occupational health and safety management practices in three certified and three noncertified co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 29 publications
1
65
0
12
Order By: Relevance
“…External services within OHS are limited by price offer, however, the result of which are problems pointing at inappropriate managerial practices. According to literature (Mohammadfam et al, 2017), it is possible to state, that until 2018, more than 100,000 companies in the world have been implementing management system of OHS according to OHSAS 18001 (currently, gradual transition to ISO 45001:2018 is expected). However, certificate should declare "quality" of OHS management.…”
Section: Resultsmentioning
confidence: 99%
“…External services within OHS are limited by price offer, however, the result of which are problems pointing at inappropriate managerial practices. According to literature (Mohammadfam et al, 2017), it is possible to state, that until 2018, more than 100,000 companies in the world have been implementing management system of OHS according to OHSAS 18001 (currently, gradual transition to ISO 45001:2018 is expected). However, certificate should declare "quality" of OHS management.…”
Section: Resultsmentioning
confidence: 99%
“…The article [7] compares the quality assessments of OSH management systems in Iran, non-certified and certified by OHSAS 18001: 2007 "Health and Safety Management System". It was revealed that occupational safety and health are certified.…”
Section: Classification Of Methods Of Estimation Of the Level Of Pmentioning
confidence: 99%
“…At most of definition that relate to safety performance to a number of injury rates, occupational accidents and illness (Mohammadfam et al, 2016, Brett & Bradley, 2008. On November 2015, case reported by Department of Occupational Safety and Health Malaysia, there is accident case involved as by https://dx.doi.org/10.15405/epsbs.2018.07.02.27 Corresponding Author: Nurulhuda Ahmad Razali Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 263 negligence of driver in Port Pasir Gudang, on July 2016, death case reported at Port Pulau Pinang.…”
Section: Problem Statementmentioning
confidence: 99%